Implementation of adaptive controls in power systems - Tay, Wei Ji (2014)
In this project, the main objective is to design a non-linear controller using the recursive backstepping method, to counteract a sudden yet temporary balanced three phase fault, and improve transient stability and maintain voltage regulation of the system. The Lyapunov function method is applied during the controller design process to ensure convergence of the system states and overall stability of the system. Existing power system equations are used to develop the single machine infinite bus model to be used in this simulation. The synchronous generator is designed based on a reduced fourth order non-linear model, otherwise known as the one axis power system model. The effectiveness of the controller, which is to improve transient response of the power system under a large fault, is demonstrated through simulation in the time domain using MatLab.